Cultural Studies on Ethnocentrism and Image of Country of Origin in the Context of Purchase Intentions - Amal, Bakhrul Khair; Samosir, Sry Lestari; ., Supsoliani (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
The objective of this research is to ascertain the influence of consumer ethnocentrism and the perceived image of a country's products on the purchasing intentions of Indonesian consumers with respect to goods originating from China. The conceptual framework of the study was formulated on the premises of ethnocentrism theory, product image perceptions, and the determinants of consumer purchase intent. This research is a qualitative descriptive research using in-depth interviews with 10 informants. The results of the study reveal that consumer ethnocentrism is attached to the purchase of domestic goods with the assumption that the goods are of high quality and have very competitive price competition with foreign goods. In Indonesia, the people already have a stigma that goods originating from China are indeed cheap. The perception of product image plays a significant role in shaping the intention to purchase imported goods from China. Indonesian enterprises have the opportunity to harness consumer ethnocentrism by designing marketing strategies that foreground nationalistic aspects, highlighting the national identity and features of domestically sold products. These strategies can be deployed as overt messages to increase the efficiency of communication or to enhance the positioning of the company's image.Â Â